New sesquiterpenoids from Petasites japonicus and Petasites tricholobus. (February 2018) - Hai, Ping; Gao, Yuan; Xiao, Chun-Gui; Jiang, Xian-Jun; Li, Xiang-Mei; Yang, Wan-Qiu; Li, Rong-Tao; Wang, Fei
Graphical abstract: Highlights: Six new sesquiterpenoids were isolated from Petasites japonicus and Petasites tricholobus . The structures of new compounds were elucidated by NMR and HRESIMS analyses. The new compound6 represented the first example of 15-noreremophilane sesquiterpenoid from the genus Petasites . Abstract: Phytochemical investigation of the whole plants of Petasites japonicus and Petasites tricholobus led to the isolation of five new bakkenolide-type sesquiterpenoids, bakkenolide-Ib (1 ), bakkenolide-IIb (2 ), bakkenolide-IIIb (3 ), bakkenolide-IVb (4 ), and bakkenolide-Vb (5 ), and a new eremophilane-type norsesquiterpenoid, petasindiol (6 ). Their structures were elucidated by NMR and HRESIMS analyses. Petasindiol (6 ) represented the first example of 15-noreremophilane sesquiterpenoid from the genus Petasites .